Delivering the Multisensory Experience of Dining-Out, for Those Dining-In, During the Covid Pandemic - Spence, Charles; Youssef, Jozef; Levitan, Carmel A. (Frontiers in Psychology, 2021)
In many parts of the world, restaurants have been forced to close in unprecedented numbers during the various Covid-19 pandemic lockdowns that have paralyzed the hospitality industry globally. This highly-challenging operating environment has led to a rapid expansion in the number of high-end restaurants offering take-away food, or home-delivery meal kits, simply in order to survive. While the market for the home delivery of food was already expanding rapidly prior to the emergence of the Covid pandemic, the explosive recent growth seen in this sector has thrown up some intriguing issues and challenges. For instance, concerns have been raised over where many of the meals that are being delivered are being prepared, given the rise of so-called “dark kitchens.” Furthermore, figuring out which elements of the high-end, fine-dining experience, and of the increasingly-popular multisensory experiential dining, can be captured by those diners who may be eating and drinking in the comfort of their own homes represents an intriguing challenge for the emerging field of gastrophysics research; one that the chefs, restaurateurs, restaurant groups, and even the food delivery companies concerned are only just beginning to get to grips with. By analyzing a number of the high-end fine-dining home food delivery options that have been offered (in the UK and in the US) in this narrative review, we highlight a number of promising directions for those wanting to optimize the at-home multisensory dining experience, wherever in the world they might be.